Chronotypes and their relationship with depression, anxiety, and fatigue among patients with multiple sclerosis in Vilnius, Lithuania - Jonušaitė, Ieva; Sakalauskaitė-Juodeikienė, Eglė; Kizlaitienė, Rasa; Giedraitienė, Nataša; Sereikė, Ieva; Liutkienė, Justina; Kaubrys, Gintaras; Jatužis, Dalius (Frontiers in Neurology, 2023)
Background Approximately half of patients with multiple sclerosis (PWMS) experience sleep disorders or changes in the circadian rhythm, that may further promote the pathogenesis of multiple sclerosis. As the prevalence of chronotypes among PWMS remains unclear, we aimed to evaluate the prevalence of chronotypes among Lithuanian PWMS; to assess the relationship of chronotypes with depression, anxiety, and fatigue symptoms; and to compare these results with those of healthy controls. Methods We enrolled 101 PWMS and 100 healthy controls. We included 130 (64.7%) and 71 (35.3%) women and men, respectively. The median age of all respondents was 39 [interquartile range (IQR) 20.75] years. Participants were assessed using general questionnaire, Horne-Östberg Morningness-Eveningness Questionnaire (MEQ), Hospital Anxiety and Depression Scale (HADS), and Shortened Fatigue Questionnaire (SFQ). Chronotypes were identified based on the total MEQ score. Results The average MEQ scores of the PWMS and control groups were 54 (IQR 15.0) and 53.5 (IQR 13), respectively, which indicated the intermediate chronotype. There was no significant between-group difference in the prevalence of chronotypes (p = 0.893). In both groups, individuals with moderate evening and intermediate chronotypes showed higher average HADS depression scores (p = 0.022). Further, in both groups, the individuals with the evening chronotype showed the highest average HADS anxiety scores (p = 0.001). The PWMS group had a higher average SFQ score than the control group (p < 0.001). High SFQ scores were more common among PWMS who had the intermediate (p < 0.001) and morning chronotypes (p = 0.011). The fatigue level was higher among healthy individuals with the evening chronotype (p < 0.001). Conclusion The most common chronotype for PWMS and healthy controls was the intermediate chronotype. Further, in both groups, higher HADS depression and anxiety scores were associated with the evening chronotype. Fatigue was more commonly found in healthy controls with the evening, and in PWMS - with intermediate and morning chronotypes.